The Influence of Product Quality on Woman Fashion Caluellathelabel of Purchase Decision Through Shopee E-commerce (A Social Science and Entrepreneurship Journal, 2023)
The purpose of this research is to determine the influence ofproduct quality on Caluellathelabel consumer purchasingdecisions. This study uses quantitative data analysis involving72 samples, namely consumer of Caluellathelabel. The resultof this research is that there is a positive and significantinfluence between product quality (X) on purchasing decision(Y). This is known by conducting a t-test which states there ispositive correlation or significant influence between productquality on purchasing decision at Caluellathelabel throughshopee e-commerce.
Keywords: Quality Product; Purchase Decisions; Caluellathelabel